Analisis Kemampuan Psikomotor Peserta Didik Pada Pelaksanaan Praktik Membersihkan Sanitary Equipment Di Edotel SMK Negeri Bandung - Lestari, Ajeng Krisma; Rohaeni, Neni; Ana, Ana (FamilyEdu: Jurnal Pendidikan Kesejahteraan Keluarga, 2017)
This research was conducted in order to solve problems in the subjects of public areas on the implementation process of sanitary equipment cleaning practice of students that which still needs to be improved because students are less in accordance with Standard Operating Procedures (SOP). The purpose of this study is to analyze the psychomotor abilities of students in the implementation process of sanitary equipment cleaning practice of students at Edotel vocational high school Bandung. The method used in this research is descriptive method. The sample used is purposive sampling, that have 33 students at least. The results of the research data showed the execution of sanitary equipment cleaning practices at Edotel 9 vocational high school Bandung wich the cleaning procedures for mirror wash basin and floor has ben found that most of the students is able to do a practice, while the toilet bowl cleaning procedure, wash basin and wall more than half students unable to doing aÂ  practice with conform to the SOP. Research Recommendations are given to teachers so should be in order to improve supervision while students doing the practice, makes the composition of SOP cleaning sanitary equipment which are then applied at Edotel 9 Vocational High School Bandung.